Correlating Estrogen Levels and Cognitive Functions in Regularly Menstruating Females of Reproductive Age Group and Post Menopausal Women of North India. - Deepti Khattar; Candy Sodhi; John Parmod; Abhilasha Dutta (Tehran University of Medical Sciences, 2015)
Objective:To correlate serum estrogen levels with cognitive functions calculated objectively as per Mini Mental State Examination (MMSE) in the females in reproductive age group and those attaining menopause. Materials and methods:This study was conducted in Christian Medical College and Hospital, Ludhiana, Punjab, India. 150 subjects (100 postmenopausal females and 50 regularly menstruating females of the reproductive age group) were included. The cognitive functions of all the females and serum estrogen levels (i.e Estradiol E2) were assessed. Results:The E2 levels in normal menstruating females were found to be higher (mean = 188.062 pg/ml) as compared to the menopausal females and the difference in E2 levels was found to be significant (p < 0.001). However, the difference in serum estrogen levels of subjects in the two menopausal groups was insignificant. MMSE, showed that scores of normal menstruating females were higher (mean score = 29.92) as compared to post menopausal females for 1-5 years (mean score = 26.72) and post menopausal females for last 6-10 years (mean score = 26.30). Conclusion:We observed that the cognition functions declined in post menopausal women, whereas the scores were higher in the women of reproductive age group, meaning thereby, that it is the serum estrogen level that is bringing about this difference. Another finding was that the decline in cognition following menopause was not progressive. Therefore, this correlation would open up the gates for the use of estrogen therapy for various neuropsychological disorders pertaining to cognition in the postmenopausal females.